Zinc requirements of broiler breeder hens. (17th October 2018) - Mayer, A N; Vieira, S L; Berwanger, E; Angel, C R; Kindlein, L; França, I; Noetzold, T L
ABSTRACT: One hundred and twenty Cobb 500 hens, 20 wk of age, were randomly allocated into individual cages with the objective of estimating their Zn requirements. The study was composed of 3 phases: adaptation to cages (basal diet), depletion (deficient diet containing 18.7 ± 0.47 ppm Zn) for 7 wk, and experimental phases. Hens were fed diets with graded increments of Zn sulfate heptahydrate (ZnSO4 ·7H2 O), totaling 18.7 ± 0.47, 50.3 ± 10.6, 77.3.0 ± 11.0, 110.2 ± 12.8, 140 ± 12.2, and 170.6 ± 13.2 ppm analyzed Zn in feeds for 12 wk (experimental phase). Requirements of Zn were done using quadratic polynomial (QP), broken line quadratic (BLQ), and exponential asymptotic (EA) models. In general, the non-linear statistical models were the ones that best fit the results in this study. Requirements obtained for hen day egg production and settable egg production were 83.3, 78.6 ppm and 61.4, 65.4 ppm for period of 33 to 36 wk, and 63.3, 53.1 and 60.4, 46.1 ppm for period of 37 to 40 wk, and 62.8, 52.8, and 67.7, 62.1 ppm for period of 41 to 44 wk, respectively, using BLQ and EA models. Total eggs and total settable eggs produced per hen had Zn requirements estimated as 75.7, 64.7 ppm, and 56.5, 41.5 ppm, respectively, for BLQ and EA models, whereas for alkaline phosphatase and eggshell percentage were 161.8, 124.9 ppm and 126.1, 122.4 ppm, using QP and BLQ models. Maximum responses for Zn in yolk for periods of 37 to 40 and 41 to 44 wk were 71.0, 78.1 and 64.5, 59.6 ppm, respectively, using BLQ and EA models. Breaking strength had Zn requirements estimated at 68.0 and 96.7 ppm, whereas eggshell palisade layer and eggshell thickness were maximized with 67.9, 67.9 ppm, and 67.7, 64.4 ppm, respectively, for BLQ and EA models. The average of all Zn requirement estimates obtained by EA and BLQ models in the present study was 72.28 ppm or 11.1 mg/hen/d.